2003
DOI: 10.1021/es034387s
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Dioxin Formation from the High-Temperature Pyrolysis of 2-Bromophenol

Abstract: Brominated hydrocarbons are the most commonly used flame retardants. Materials containing brominated hydrocarbons are frequently disposed in municipal and hazardous waste incinerators as well as being subjected to thermal reaction in accidental fires. This results in the potential for formation of brominated dioxins and other hazardous combustion byproducts. In contrast to chlorinated hydrocarbons, the reactions of brominated hydrocarbons have been studied only minimally. As a model brominated hydrocarbon that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
69
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 41 publications
14
69
2
Order By: Relevance
“…• by H • (Evans and Dellinger, 2003;Evans and Dellinger, 2005). As observed in the present study, they also reported that the formation of benzene occurred at lower yields and higher temperatures than the formation of phenol, and that this was consistent with the more endothermic displacement of OH • by H • from phenol to form benzene, in comparison to the previous mechanism proposed for the formation of phenol.…”
Section: Analysis By Gc-mssupporting
confidence: 92%
“…• by H • (Evans and Dellinger, 2003;Evans and Dellinger, 2005). As observed in the present study, they also reported that the formation of benzene occurred at lower yields and higher temperatures than the formation of phenol, and that this was consistent with the more endothermic displacement of OH • by H • from phenol to form benzene, in comparison to the previous mechanism proposed for the formation of phenol.…”
Section: Analysis By Gc-mssupporting
confidence: 92%
“…Equation IV was obtained by simplification of a formula derived by Mozurkewich and Benson 37 (equation 12 of reference 37) for reactions proceeding over shallow potential energy wells. The simplification resulted from the above mentioned assumption of predominant dissociation of the OH···Br 2 complexes to OH + Br 2 and from an approximate treatment of the effects of angular momentum (J) conservation where the rate coefficient value obtained for J = 0 is multiplied by the ratio of the partition functions of the two-dimensional rotational (inactive) degrees of freedom of the transition state and the active molecule. The latter ratio (1.2) is close to unity, which justifies the use of the approximation.…”
Section: Potential Energy Surface and Transition State Theory Momentioning
confidence: 99%
“…High-temperature pyrolysis of bromophenols leads to dioxin formation. 14) Hence the development of a biological purification system is one alternative to reduce levels of exposure to 2,4,6-TBP.…”
mentioning
confidence: 99%